Assessing public awareness of clubfoot and knowledge about the importance of early childhood treatment: a cross-sectional survey - Abdulmonem Alsiddiky; Salman Alrwibaah; Abdulrahman Alqahtani; Abdulmalek Alnujidi; Abdullah Alhomaidhi; Abdulla Almasoud; Raheef Alatassi (BMC, 2019)
Abstract Background Clubfoot is a treatable abnormality that can be managed with early intervention. However, there is a lack of public knowledge regarding clubfoot, which can delay treatment. This study aimed to assess the public awareness of clubfoot and knowledge regarding the importance of treatment in early childhood. Methods This cross-sectional survey spanned 6 months, from June through November 2018, and involved persons living in Saudi Arabia. To collect data on public awareness of clubfoot risk factors, treatment, and prognosis, a questionnaire was developed by orthopedic experts and disseminated online. The target population included people of both genders and all age groups from the general population, regardless of their knowledge of someone with clubfoot. Results By the end of the study period, 746 participants completed the online survey. In total, 520 of the respondents (69.7%) had never heard about clubfoot syndrome. Among the participants, 5.4% had a child with clubfoot syndrome and 4.6% were aware of clubfoot because they had an affected child. The top resource accessed by respondents for obtaining knowledge about clubfoot was social media channels (38.4%), followed by obtaining knowledge from relatives and friends (19.9%). The most reported perceived cause of clubfoot was hereditary and genetic disorders (58.4%), followed by neurological disorders (39.9%). Conclusions Results show that there is low public knowledge of clubfoot which may be attributed to a lack of awareness campaigns. We recommend increasing awareness regarding clubfoot through social media platforms and public campaigns in key locations, such as malls, as this may encourage people to seek early treatment. This is important because early management of clubfoot is less invasive and with regular follow-up, leads to better patient outcomes.